FACTORS FORMING RELATIONSHIPS AND EVERYDAY RUSSIAN AND BELARUSIANS - Tuzhba, Emir Nodarievich (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Purpose. It consists in the analysis of the factors influencing the process of interaction, the nature of relationships and everyday life of the Russian and Belarusian communities. Methodology. Use the ideas of the system, interactionist, phenomenological and socio-psychological approaches. The empirical base totaled questionnaire data of the Russian population of the Krasnodar Territory; secondary analysis of sociological data of Russian and Belarusian research teams on studies. Results. Identified and analyzed factors of relationships and the culture of everyday life, especially their impact on the processes of interaction between Russian and Belarusian ethnic communities. Practical implications. Knowledge of the factors and content of the mutual influence of ethnic and cultural practices of the ethnic communities of Belarus and Russia will help to predict the interaction processes contribute to their consolidation and integration.